Ancestral diets and nutrition - Cumo, Christopher, author.
1 online resource (1 volume)
Keywords: Ancestral Diets and Nutrition supplies dietary advice based on the study of prehuman and human populations worldwide over the last two million years. This thorough, accessible book uses prehistory and history as a laboratory for testing the health effects of various foods. It examines all food groups by drawing evidence from skeletons and their teeth, middens, and coprolites along with written records where they exist to determine peoples' health and diet. Fully illustrated and grounded in extensive research, this book enhances knowledge about diet, nutrition, and health. It appeals to practitioners in medicine, nutrition, anthropology, biology, chemistry, economics, and history, and those seeking a clear explanation of what humans have eaten across the ages and what we should eat now. Features: Sixteen chapters examine fat, sweeteners, grains, roots and tubers, fruits, vegetables, and animal and plant sources of protein. Integrates information about diet, nutrition, and health from ancient, medieval, modern and current sources, drawing from the natural sciences, social sciences, and humanities. Provides comprehensive coverage based on the study of several hundred sources and the provision of over 2,000 footnotes. Presents practical information to help shape readers' next meal through recommendations of what to eat and what to avoid.